(E)-1, 2-Di(thiophen-2-yl)ethene based high mobility polymer for efficient photovoltaic devices without any post treatment. Issue 72 (18th July 2016) - Ren, Junzhen; Zhang, Yongchao; Liu, Fushuai; Yan, Yan; Qiu, Meng; Roy, V. A. L.; Zheng, Huilin; Sun, Mingliang; Yang, Renqiang
Abstract : The ethene based polymer shows better photovoltaic performance. Abstract : In order to investigate the effect of an ( E )-1, 2-di(thiophen-2-yl)ethene (TVT) unit on the hole mobility and photovoltaic properties of dithienyl-difluorobenzothiadiazole (DTBT) based polymers, two conjugated polymersPDT-DTBT-DT (thiophene backboned) andPTVT-DTBT-DT (TVT backboned) were synthesized. Compared toPDT-DTBT-DT, the backbone conformation ofPTVT-DTBT-DT could be well modulated by the TVT unit, leading to an extended conjugation length and strengthened intermolecular interaction. Interestingly, it's found that the ultraviolet-visible (UV-vis) absorption peaks of thePTVT-DTBT-DT film was blue-shifted compared to that of the solution. The organic field-effect transistor (OFETs) characterization showed thatPTVT-DTBT-DT possessed a high hole mobility of 0.12 cm 2 V −1 s −1, which was higher than that of the counterpartPDT-DTBT-DT (0.04 cm 2 V −1 s −1 ). Through simplified device optimization without any additives and annealing treatment, a power conversion efficiency (PCE) of 7.86% was achieved forPTVT-DTBT-DT with a short-circuit current density ( J sc ) of 16.33 mA cm −2 and a fill factor (FF) of 68.92%, which is higher the PCE of 7.29% ofPDT-DTBT-DT with a J sc of 15.60 mA cm −2 and a FF of 66.62%. The PCE of 7.86% is among the highest PCEs reported for devices fabricated without any additives and thermal annealing treatment. The results revealed thatPTVT-DTBT-DT as an ideal conjugated polymer could provide a greater possibility for the commercial application of PSCs, especially in terms of low cost and manufacturing convenience.